2011
DOI: 10.1055/s-0030-1270427
|View full text |Cite
|
Sign up to set email alerts
|

Rhytidectomy: Principles and Practice Emphasizing Safety

Abstract: There is an unprecedented acceptance of rhytidectomy by today's society. No longer limited to the affluent few, middle class citizens are devoting their expendable income to achieve a more youthful appearance that is natural and inconspicuous. Despite recent difficult economic times, the mindset of the working population continues to be welcoming of rhytidectomy as a way to achieve a refreshed look while expecting minimal downtime and morbidity. To achieve these results, the current literature has described an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…[19][20][21] In the mid-1990s, facelifts and rejuvenation operations were becoming increasingly technically demanding and risky due to exposure of the facial nerve branches and extensive soft tissue dissections. 22 These complex procedures yielded superb outcomes in expert hands; however, often patients operated on by less-experienced surgeons experienced prolonged postoperative edema, sensory or motor nerve injury, and facial asymmetry. 22,23 Today there are many facelift approaches, such as the deep plane facelift, composite facelift (which involves repositioning and fixation of the orbicularis oculi muscle), midfacelift, minifacelift, thread lift, periosteal facelift, skin-only facelift, and minimal access cranial suspension lift.…”
Section: Faceliftmentioning
confidence: 99%
“…[19][20][21] In the mid-1990s, facelifts and rejuvenation operations were becoming increasingly technically demanding and risky due to exposure of the facial nerve branches and extensive soft tissue dissections. 22 These complex procedures yielded superb outcomes in expert hands; however, often patients operated on by less-experienced surgeons experienced prolonged postoperative edema, sensory or motor nerve injury, and facial asymmetry. 22,23 Today there are many facelift approaches, such as the deep plane facelift, composite facelift (which involves repositioning and fixation of the orbicularis oculi muscle), midfacelift, minifacelift, thread lift, periosteal facelift, skin-only facelift, and minimal access cranial suspension lift.…”
Section: Faceliftmentioning
confidence: 99%
“…elective nature of this procedure 15,16 places added emphasis on obtaining reliable and comprehensible information. In our institutional experience, patients interested in this procedure typically seek information on the internet prior to the initial consultation or subsequent visits.…”
mentioning
confidence: 99%
“…In fact, no published studies are identified that provide a critical analysis of YouTube videos on rhytidectomy, a common facial plastic surgery procedure. The elective nature of this procedure 15,16 places added emphasis on obtaining reliable and comprehensible information. In our institutional experience, patients interested in this procedure typically seek information on the Internet prior to the initial consultation or subsequent visits.…”
mentioning
confidence: 99%